Dreams of Care and Consolation: Reflections of the Funeral Rites in the Dream Narratives - Ivanauskaitė - Šeibutienė, Vita (Tautosakos darbai, 2022)
The departed, their visits, requests, and warnings constitute the main theme in the dream narratives by the Lithuanians and other peoples. The article focuses on the relationship between folkloric dream narratives and ancient funeral rites. The research sources include oneiric narratives by the Lithuanians and their neighboring Slavic peoples recorded from the end of the 19th to the beginning of the 21st century. Ethnographic accounts of ancient funeral ceremonies and funeral laments are also employed. For a more thorough investigation, several oneiric motives undoubtedly related to the funeral rites have been selected, including taboos on inviting the deceased to appear in relatives’ dreams and advice for mothers not to weep excessively and not to mourn their departed children too much. Some recorded narratives depict the departed children appearing in dreams and begging not to cry for them so much, because they are drowning in tears, are soaking wet, or have difficulties with carrying vessels overflowing with their mother’s tears. Another especially popular motive in the dream narratives is the requests from the deceased to “give back” some things that belong to them, or certain missing grave goods, e.g. shoes. The ethnographic funeral accounts from the 19th century repeatedly state the requirement for the deceased to be buried wearing shoes. If the shoes cannot be put on, they have to be placed inside the coffin. This ritual requirement finds its peculiar reflection in the dream narratives depicting the deceased appearing barefoot in dreams and demanding to “give back the shoes”. In order to fulfill this request, relatives of the departed person “send over” the missing shoes by burying them into the grave separately or by placing them into the coffin with another deceased. This particular focus on the shoes of the departed in the traditional culture (including the dream narratives) results from the notion of death as a journey. Dream narratives are regarded in this study as an inherent part of the set of funeral rites. The author maintains that the narratives depicting the deceased manifesting in dreams and requesting that some things are returned to them, or begging relatives to stop weeping and mourning, in fact testify that some rituals have not been performed in full or have been performed improperly, thus thwarting the clear separation of the deceased from the world of the living. In turn, responses of the dreamers that are also described in these narratives embody a symbolic continuation of the ritual until it is finally completed.